Gastrostomy tube placement among infants with hypoplastic left heart syndrome undergoing stage 1 palliation. (13th May 2018) - Prodhan, Parthak; Tang, Xinyu; Gossett, Jeffrey; Beam, Brandon; Simsic, Janet; Ghanayem, Nancy; ElHassan, Nahed O.
Abstract: Objective: Different feeding strategies have been suggested to improve growth and survival of infants with hypoplastic left heart syndrome following stage 1 palliation. The study objective was to assess hospital mortality following stage 1 palliation among infants with hypoplastic left heart syndrome who had two feeding modalities, gastrostomy tube vs no gastrostomy tube. Design: Retrospective study design. Setting: Multicenter pediatric heath information system database. Patient: About 4287 patients with hypoplastic left heart syndrome who underwent stage 1 Norwood procedure from 2004 through 2013. Infants who had gastrostomy tube with or without fundoplication procedure were identified and their clinical characteristics were compared. Intervention: None. Outcomes Measures: The primary outcome was discharge hospital mortality following stage 1 palliation. Results: About 1214 patients who underwent stage 1 palliation had gastrostomy tube placement prior to hospital discharge. About 881 only had this procedure, while 333 patients also underwent fundoplication. Infants who had a gastrostomy tube placement vs no gastrostomy procedure had longer hospital stay, but significantly lower hospital mortality (5% vs 19%, P < .001). Hospital mortality was lower in infants who had only gastrostomy vs gastrostomy with fundoplication procedure (4% vs 8%, P = .004). In the multivariable analysis, gastrostomy procedure was associated with a higher likelihood of survival to hospital discharge (HR: 0.06, CI [0.04, 0.1]), whereas additional fundoplication procedure increased the risk of mortality (HR: 2.77, CI [1.52, 5.04]). Conclusions: The gastrostomy procedure did not place infants with hypoplastic left heart syndrome at higher risk of mortality. These infants should be considered for gastrostomy tube placement if they had persistent difficulty in oral feeding following stage 1 palliation.